Review of The Lexical Domain of Beauty and its Metaphors in the Anglo-Saxon Formulaic Style. By Francisco Javier Minaya Gómes - Rzonsowska, Natalia (Studia Anglica Posnaniensia, 2023)
Review of The Lexical Domain of Beauty and its Metaphors in the Anglo-Saxon Formulaic Style. By Francisco Javier Minaya Gómes